Die ekstraksie van die nitratokompleks van serium-III deur tri-oktielamien - Pretorius, S. C. W.(Stephanus Christiaan Willem) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 1967.